2011
DOI: 10.1002/anie.201106706
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Borylation Reactions of Alkynes and Arynes

Abstract: One, two, three, four: A copper(I)–phosphine complex catalyzes the diborylation of alkynes and arynes, and the tri‐ or tetraborylation of propargyl ethers (see scheme; pin=pinacolato). In the latter cases, the CO bond(s) as well as the CC bond are borylated in one pot. Furthermore, a diborylation product serves as an intermediate in the efficient synthesis of ortho‐terphenyls with pharmacological activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
86
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(90 citation statements)
references
References 41 publications
0
86
0
4
Order By: Relevance
“…Synthesis of alkenyldiboronates is typically accomplished by diboration of terminal or internal alkynes and is often promoted by transition-metal catalysts, 7 base, 8 Lewis acid, 9 and in some cases proceeds in the absence of catalysts. 10 Regardless of the synthetic route, these methods almost exclusively result in 1,2-difunctionalization, 11 a common reactivity mode for addition to C–C multiple bonds (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of alkenyldiboronates is typically accomplished by diboration of terminal or internal alkynes and is often promoted by transition-metal catalysts, 7 base, 8 Lewis acid, 9 and in some cases proceeds in the absence of catalysts. 10 Regardless of the synthetic route, these methods almost exclusively result in 1,2-difunctionalization, 11 a common reactivity mode for addition to C–C multiple bonds (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Basierend auf unseren experimentellen Beobachtungen (siehe auch Schema S2 und S3) und vorangegangenen Beispielen von verwandten katalytischen dehydrierenden Borylierungsprozessen wird in Schema ein Mechanismus vorgeschlagen. Das terminale Alkin reagiert mit [L n CuOAc], welches zuvor aus Cu(OAc) 2 und einem Phosphanliganden gebildet wird, gefolgt von einer Reduktion, in der das Alkinylkupfer‐Intermediat B erhalten wird . Das Intermediat B geht eine σ‐Bindungsmetathese mit B 2 pin 2 ein und liefert das Alkinylboronat 4 sowie den Cu‐Borylkomplex C .…”
Section: Methodsunclassified
“…Das Intermediat B geht eine σ‐Bindungsmetathese mit B 2 pin 2 ein und liefert das Alkinylboronat 4 sowie den Cu‐Borylkomplex C . Das Einbringen des Alkinylboronats 4 in eine Cu‐B‐Bindung von C führt zur Bildung des Alkenyl‐Kupferkomplexes D , der in einer σ‐Bindungsmetathese mit B 2 pin 2 das gewünschte 1,1,2‐Triborylalken 2 bildet . Die Hydroborierung von Acrylnitril ist schneller als die von Alkinen, wodurch die Alkinhydroborierung als Nebenreaktion unterdrückt und der Triborierungsprozess effizienter wird.…”
Section: Methodsunclassified
“…34 Yoshida subsequently showed that both the boryl groups could be added to alkynes directly if higher temperatures were employed and proton sources were absent from the reaction mixture. 60 …”
Section: Kohmentioning
confidence: 99%